Analysis Of Fee Based Income And Interest Earningson Net Profit Commercial Bank Listed On The Indonesian Stock Exchange - Christy Mariana Pandiangan; Syahrial Hasanuddin Pohan; Kasim Siyo (Jurnal Scientia, 2024)
The aim of this research is to investigate the impact of fee based income and interest income on net profit at Commercial Banks listed on the Indonesia Stock Exchange. Data obtained from www.idx.co.id with a time span of 2018-2023. The research was conducted in 2024 with a population of 44 companies and a sample of 26 companies. Analysis uses quantitative data via Eviews 9 with panel regression. The results show that interest income has a positive and significant impact on net profit, while fee based income is not significant. Simultaneously, both variables have a positive and significant impact on net profit, with a total contribution of 66.09%.